PKM PELATIHAN DAN PENDAMPINGAN GURU SMP HARAPAN SUNGAILIAT DALAM MENGEMBANGKAN PEMBELAJARAN BERBASIS LMS MOODLE DAN GOOGLE CLASSROOM - Parulian Silalahi; Yang Agita Rindri; Charlotha Charlotha (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Moodle and Classroom are some of the alternative learning media that can be used by teachers in improving the learning process more effectively. However, many teachers still do not understand how to utilize e-learning in learning process. This program aims to improve the ability of teachers to utilize ICT for learning through Moodle and Classroom. The program activity includes the development of Moodle-based e-learning and training for teachers at SMP Harapan Sungailiat. The training results show that teachers’ skills in using the e-learning module are increase. The training questionnaire showed that 98% of the participants were able to use e-learning. The percentage of participants who quite agree that they are skilled at using e-learning is 52%. Meanwhile, 41% agree that they are skilled at using e-learning, and 6% strongly agree that they are skilled at using e-learning.